Idosos apresentam menor capacidade sudorípara do que jovens durante exercício de intensidade autorregulada sob o sol - Renata Lane de Freitas Passos (2011)
It has been proposed that the sweating capacity is related to the aerobic capacity, which would be reduced with aging. However, little is known about the effects of aging on the sweating and thermoregulatory capacities in elderly men and women. Objective: To compare thermoregulatory responses between young and older adults of both sexes. Methods: After approval by the Research Ethics Committee of UFMG (ETIC 0498.0.203.000-09), 47 volunteers, 24 men (M) and 23 women (W), where 24 were young [12 men (YM) and 12 women (YW) (age: 25.6 } 0.5 and 24.8 } 0.5 years, body mass: 76.4 } 2.0 and 56.5 } 1.2 kg, BSA.mass-1.100: 2,6 } 0,0 and 2,8 } 0,0 m2.kg-1 and aerobic capacity: 46,6 } 1,4 and 38,2 } 1,3 ml.kg-1.min-1, respectively)] and 23 were old subjects [12 men (OM) and 11 women (OW) (age 66.4 } 1.1 and 63.3 } 1.1 years, body mass: 65.4 } 2.3 and 64.1 } 3.3 kg, BSA.mass-1.100: 2,6 } 0,0 e 2,6 } 0,0 m2.kg-1 and aerobic capacity: 36.4 } 2.0 and 30.2 } 1.7 ml.kg-1.min-1, respectively)], consideredhealthy and fit for physical activity, ran a total of 6 km, in four steps of 1.5 km with intervals of 2 minutes at highest voluntary speed possible (exercise self-paced). The total exercise time (TET, in min) to perform the route, average speed (VM in km/h), energy expenditure (EE, kcal/min),%heart rate (MHR,%), average heart rate (FCmed in bpm.min-1), delta rectal temperature (¢ Tret, in C), mean skin temperature during exercise (TmpEX, in C), total sweat rate (TS, in gm- 2.min-1), number of activated sweat glands (GSA.cm-2), sweating by GSA (g.min-1.GSA-1), the physiological strain index (PSI) and the average index wet bulb globe temperature (WBGT, in C) were measured. Statistical analysis: ne-way ANOVA and post hoc test Student Newman Keuls or Tukey were used to compare the results. To investigate the relationship betweenvariables, we used Pearson correlation and the significance was set at ¿ = 5%. Results: The WBGT was not different between the experimental conditions for all groups (25.69 } 0.14o C). The TET was lower in YM in comparison with the groups OM and OW, and the OW group washigher than the other groups (YM: 30.6 } 1.7 min, OM: 41.8 } 3.7 min YM: 37.2 } 1,4 min, OW: 51.6 } 4.0 min; p<0.05). The percentage of the MHR during the exercise was not different between groups (YM: 90.7 } 1.2%, OM: 89.9 } 1.8% YW: 91.8 } 0.7%, OW: 88, 8 } 1.8%; p>0,05). The EE was higher in the YM (15.5 } 0.8 kcal.min-1; p<0,05) and was not different among the other groups (OM: 9.9 } 0.6 kcal.min-1, YW: 9.5 } 0.3 kcal.min-1, OW: 8.2 } 0.5 kcal.min-1;p>0,05). PSI was not different between groups (YM: 8.2 } 0.3, OM: 7.3 } 0.2, YW: 8.0 } 0.2, OW: 7.4 } 0.2; p>0,05). However, there was a trend for difference between groups (p = 0.052). Regardless of sex, PSI was higher in young compared with old (young: 8.08 } 0.19, old: 7.37 } 0.14; p<0.05).The total sweat rate was lower in the old group in both sexes (YM: 20.6 }2.1 g.m-2.min-1, OM: 14.3 } 2.0 g.m-2.min-1, YW: 15.3 } 1.1.m-2.min-1, OW: 9.6 } 1.2 g.m-2.min-1; p<0,05), and aerobic capacity is the main factor for this reduction (r2 = 0.67, p <0.001). The reduction in TS for the OM can also be explained in part by reducing (p<0.05) sweating per gland(0.02 } 0.00 g.min-1.GSA-1) compared with YM (0.03 } 0.00.min-1.GSA-1), which was not observed in women with aging (YW: 0.02 } 0.00 g.min-1.GSA-1 and OW: 0.02 } 0.00 g.m-2.min- 1.GSA-1; p>0.05). Another explanation for the reduction of TS observed in the elderly female group would be to decrease the number of GSA (OW: 54 } 6 GSA.cm-2 vs. YW: 72 } 6 GSA.cm-2; p<0.05), but this finding was not repeated in the elderly male (OM : 74 } 6 GSA.cm-2 vs. YM: 79 }7 GSA.cm-2; p>0.05). The TmpEX was higher (p<0.05) in women (YW: 37.6 } 0.1o C and OW: 37.2 } 0.1o C) compared with men (YM: 34.8 } 0.2o C and OM: 33.7 } 0.2o C) in both age groups.The ¢Tret was not different between groups (YM: 1.8 } 0.1o C, OM: 1.5 } 0.1o C, YW, 1.6 } 0.1o C, OW: 1.5 } 0.1o C). Conclusions: During the self-paced exercise, the elderly of both sexes had lower sweat rates compared with young people in both sexes. The lower aerobic capacity of the elderly was the main factor for decreased sweating. The number of active glands, sweat rate per gland active and mean skin temperature during exercise respond to exercise differently between the sexes.